#TITLE_ALTERNATIVE# - GILANG RAMADHAN (NIM : 10309013); Pembimbing : Dr. Hakim L. Malasan, DHIMAZ
Several new times of minimum from eclipsing binary AO Velorum observed photometrically. Observations were made using PROMPT (Panchromatic Robotic Optical Monitoring and Polarimetry Telescope) in CTIO (Cerro Tololo Inter-American Observatory), Chile, on the period between 15 February 2013 until 29 March 2013. This research is part of BIMA (Eclipsing BInaries MiniMA Monitoring) project's activities. BIMA project is joint project between Bosscha Observatory,Indonesia, and National Astronomical Reseach Institute of Thailand (NARIT). O(Observed) - C(Calculated) diagram constructed by combining new times of minimum found in the literature and using an adopted linear ephemeris. From O-C diagram analysis we found that AO Velorum shows apsidal motion and we revealed existence of third body. Our main aim is to analyze apsidal motion and third body orbital elements in AO Velorum. Analysis of O-C diagram shows that line of apsides (major axis) of AO Velorum orbit rotates with apsidal motion rate ̇ = 11.20 / year and the binary system orbiting the third body with period 33.2 years.